Low-Carbohydrate Tolerant LAB Strains Identified from Rumen Fluid: Investigation of Probiotic Activity and Legume Silage Fermentation - Palaniselvam Kuppusamy; Dahye Kim; Ilavenil Soundharrajan; Hyung Soo Park; Jeong Sung Jung; Seung Hak Yang; Ki Choon Choi (Microorganisms, 2020)
The objective of this study was to isolate and characterize lactic acid bacteria (LAB) with low carbohydrate tolerance from rumen fluid and to elucidate their probiotic properties and the quality of fermentation of Medicago sativa L. and Trifolium incarnatum L. silage in vitro. We isolated 39 LAB strains and screened for growth in MRS broth and a low-carbohydrate supplemented medium; among them, two strains, Lactiplantibacillus plantarum (Lactobacillus plantarum) RJ1 and Pediococcus pentosaceus S22, were able to grow faster in the low-carbohydrate medium. Both strains have promising probiotic characteristics including antagonistic activity against P. aeruginosa, E. coli, S. aureus, and E. faecalis; the ability to survive in simulated gastric-intestinal fluid; tolerance to bile salts; and proteolytic activity. Furthermore, an in vitro silage fermentation study revealed that alfalfa and crimson clover silage inoculated with RJ1 and S22 showed significantly decreased pH and an increased LAB population at the end of fermentation. Also, the highest lactic acid production was noted (p < 0.05) in LAB-inoculated silage vs. non-inoculated legume silage at high moisture. Overall, the data suggest that RJ1 and S22 could be effective strains for fermentation of legume silage.